Diseño de sistema SCADA para el control y monitoreo de la caldera ch3-400-250-3lg/g en la empresa Cymascotas SAS. (2020)
One of the most used equipment in the area of manufacturing, are boilers, equipment responsible for generating steam of industrial quality, which is used in different processes, in the specific case of the CYMACOSTA cardboard factory located in Santa Marta Colombia, the steam the crucial for the process of corrugation of the cardboard, being then one of the most important equipment needed in the production chain , these boilers must be monitored by specialized systems that control temperatures, pressure and liquid levels, among other safety and operation components. On the other hand it is known that Santa Marta does not have an adequate supply in the energy system, which causes poor functioning of the equipment, therefore losses in manufacturing processes and high occupational risks. The purpose of the research is to provide a permanent remote monitoring system of all control and security variables